Narrow Band Gap Ternary Absorber Layer for Solar Cell for Small Business Enterprises in Equatorial Africa - Mosiori, Cliff Orori (Engineering International, 2017)
According to recent studies, on the Daily nation newspaper, in Kenya of 6th January 2017 featured the story, the number of people doing the same thing in surrounding villages was so high that many of them had to leave their phones behind at the charging centre (for up to three days) before returning to pick them. To fight darkness, up to 80 percent of Africans depend on personal generators, candles and kerosene (paraffin) lamps to provide basic lighting. Let’s not even talk about all the other things we desperately need electricity for – iron clothes, pump water, charge mobile phones etc. In this article, we shall focus on the types of solar cell materials that can be used to fabricate solar cell to be installed on roof tops to generate electricity used by individuals and households. Photovoltaic devices are used to convert solar radiation energy into electrical forms of energy for various uses. Current research is geared towards using thin films with wide band gaps to allow optimum penetration of radiation within the VIS - NIR region. Inorganic wide band gap, CdxZn1-xS thin films and narrow band gap, PbS thin films were optimized through chemical solution technique in this study. Wide band gap thin films of CdxZn1-xS were grown at about 820C while those of narrow band gap thin films of PbS were grown at room temperature utilizing aqueous conditions. Their optical constants were investigated and found to be suitable for solar cells applications.
Keywords: Solar cell; small business enterprise; energy demand; CdxZn1-xS; Band gap; resistivity; Open Voltage; VIS - NIR region